2001
DOI: 10.1086/316930
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of 3243 A→G mtDNA Mutation from Blood in MELAS Syndrome: A Longitudinal Study

Abstract: It is widely held that changes in the distribution of mutant mtDNAs underlie the progressive nature of mtDNA diseases, but there are few data documenting such changes. We compared the levels of 3243 A-->G mutant mtDNA in blood at birth from Guthrie cards and at the time of diagnosis in a blood DNA sample from patients with mitochondrial encephalopathy, lactic acidosis, and strokelike episodes (MELAS) syndrome. Paired blood DNA samples separated by 9-19 years were obtained from six patients with MELAS. Quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(166 citation statements)
references
References 15 publications
13
149
1
3
Order By: Relevance
“…Our results are supported by an observation of a decrease of mtDNA with the A3243G mutation in leukocytes in two DNA samplings within a time period of 1.5 ± 6 years 25 and when comparing blood samples taken at birth (Guthrie cards) and at the time of diagnosis, in five patients with the MELAS syndrome. 26 A similar decrease in heteroplasmy level was observed when studying the 3460 LHON (Leber hereditary optic neuropathy) mtDNA mutation over a time period of 5 ± 6 years. 27 We have previously analysed cervical cell samples from four healthy women with heteroplasmic, non-pathogenic nucleotide variations at position 309 or 16189 of the control region of mtDNA.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our results are supported by an observation of a decrease of mtDNA with the A3243G mutation in leukocytes in two DNA samplings within a time period of 1.5 ± 6 years 25 and when comparing blood samples taken at birth (Guthrie cards) and at the time of diagnosis, in five patients with the MELAS syndrome. 26 A similar decrease in heteroplasmy level was observed when studying the 3460 LHON (Leber hereditary optic neuropathy) mtDNA mutation over a time period of 5 ± 6 years. 27 We have previously analysed cervical cell samples from four healthy women with heteroplasmic, non-pathogenic nucleotide variations at position 309 or 16189 of the control region of mtDNA.…”
Section: Discussionsupporting
confidence: 60%
“…When comparing the results from two previous studies on peripheral blood by Rahman et al, 26 and Howell et al, 27 we find that a relative rate of decline in the level of heteroplasmy (average of 2.5% and 5.3% with CV:s of 0.34 and 0.48 respectively) better fit the data than an absolute rate of decline (average of 1.3% and 1.1% with CV:s of 0.37 and 0.60). This is not the case for a third study by, 't Hart et al 25 where the relative rate of decline is 3.9% (CV, 1.44) in contrast to an absolute rate of decline of 0.69% (CV, 0.88).…”
Section: European Journal Of Human Geneticsmentioning
confidence: 97%
“…Blood carrying the deleterious "MELAS" mutation (m.3243A>G) has been shown to decrease its mutation load with age [23]. Conversely muscle seems to progressively increase with age its mutation load in patients with inherited mtDNA deletion [24] or point mutation [25].…”
Section: Clinical Observationsmentioning
confidence: 99%
“…Previous studies have indicated that the amount of the mutant m.3243A[G mtDNA form decreases by age in leukocytes [13,14], and therefore in cases in which a suspicion for presence of m.3243A[G mutations arose, we tried to obtain a second sample of urine epithelial cells for mtDNA analysis, as these cells have shown to represent well the overall tissue mutant mtDNA load. The presence of the mutation and quantitation of mtDNA heteroplasmy was performed by PCR-amplification and solid-phase minisequencing methodology, as previously described [15].…”
Section: Cell Materials and Dna-analysismentioning
confidence: 99%